BACILLUS CEREUS IN FOOD: PARTIAL PURIFICATION AND CHARACTERIZATION OF HEMOLYSIN - Shobana C S; Lakkumi Venmal A K; Amsaveni P (Tropical Life Sciences Research, 2008)
Bacillus cereus is an aerobic spore former commonly found in soil, vegetables and in many raw, and processed foods. Consumption of foods that contain large numbers of B. cereus may result in food poisoning. Although, certain physiological and cultural characteristics are necessary for identifying B. cereus, its enterotoxigenicity indicates whether a suspect strain may be a public health hazard. Out of 75 food samples tested, we obtained 57 hemolytic strains of B. cereus. On further screening based on the antibiotic susceptibility pattern, three strains viz., B. cereus PCBC-06, B. cereus PCBC-52 and B. cereus PCBC-57 were selected and investigated for their growth pattern. Of all the three strains, B. cereus PCBC-06 exhibited good growth pattern. Test strains grew after the treatment at 40, 50, 60, 70, 80 and 90ºC and were killed only after treating at 121ºC for 20 min at 15 lb/sq. in. The optimum pH and glucose concentration for the growth of all strains were between 7.0 and 9.0, and 0.5%, respectively. B. cereus PCBC-06, B. cereus PCBC-52 and B. cereus PCBC-57 optimally grew at salt concentration of 0.75%, 0.5% and 0.25%, respectively. The heat resistance measurements exhibited that the test strains failed to grow at 2°C and the spore D90 value ranged from 5.40 to 5.50 min. B. cereus PCBC-06 was subjected to protein studies and its protein accumulation was directly proportional to its growth. In gel diffusion assay, discontinuous pattern of hemolysis by the crude toxin was observed and the zones measured 0.6 cm, 0.8 cm and 0.9 cm at 20 min, 65 min and 100 min, respectively. Hemolysin was produced by dialyzing membrane technique and partially purified hemolysin by ammonium sulphate precipitation had protein content of 44 ?g/ml of sample. SDS-PAGE of the crude hemolysin showed four conspicuous bands of molecular weight 70 000, 68 000, and 57 000 and 43 000.